Development of Learning Media Based on Geogebra-Assisted Inquiry Learning Models to Improve Students' Mathematical Reasoning Abilities - Silalahi, Joshua Pandapotan; Siagian, Pargaulan; Mukhtar, Mukhtar (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to determine the validity, practicality and effectiveness of Geogebra-assisted inquiry learning model-based learning tools developed to improve students' mathematical reasoning. This research is included in development research. This research will be carried out at SMA Negeri 1 Gebang, Jl. Diponogoro, Pekan Gebang, District. Gebang, Kab. Langkat, North Sumatra 20856 for students in class XI Semester I for the 2023/2024 academic year. The research results show that: 1) The tools developed are valid with (a) average validation results for lesson plans of 4.34, teaching materials of 4.23, Student Worksheets of 4.24, mathematical reasoning ability tests of 4.18 . 2) The device developed was categorized as practical with the results of trial I scoring an average of 3.07 ("Medium" category), while in trial II the average was 4.04 in the "High" category; 3) the tool developed is categorized as effective because (a) Achievement of the final test of students' Mathematical Reasoning ability in trial I was 52% with the number of students as many as 21 students (58.33%) being declared complete and trial II 30 students completed or 83 .34%. (b) the student response questionnaire score in trial I was 89% and in trial II was 95%. 4) there was an increase in students' mathematical reasoning abilities with a score of 0.28 (0.3 <g≤0.7) in trial 1 and trial II there was an increase in scores with "medium" criteria with a score of 0.67 (0.3 < N-Gain ≤0.7).